Effects of chlorine dioxide fumigation on redox balancing potential of antioxidative ascorbate-glutathione cycle in ‘Daw’ longan fruit during storage - Chumyam A. (2017)
© 2017 Elsevier B.V. Redox status in ascorbate-glutathione (ASA-GSH) cycle plays a pivotal role in plant responses to physiological and environmental changes. The change of ASA-GSH redox potential is associate with oxidative stress leading to plant senescence. The present study was aimed to investigate the effects of gaseous ClO 2 on the redox status involved in delaying fruit senescence during storage of harvested longan fruit (Dimocarpus longan Lour. cv. Daw). Fresh longan fruit were fumigated with 10 mg/L ClO 2 for 10 min, packed into cardboard boxes and stored at room temperature for 7 d. The results show that redox status of the fruit determined by ASA/DHA, GSH/GSSG and NADPH/NADP ratios decreased steadily in ClO 2 untreated control group during storage. On the contrary, those ratios increased immediately after ClO 2 treatment before declining steadily afterwards. The activities of NADPH-generating dehydrogenases including glucose-6-phosphate dehydrogenase and 6-phosphogluconate dehydrogenase, and ASA-GSH cycle enzymes including ascorbate peroxidase, monodehydroascorbate reductase, dehydroascorbate reductase and glutathione reductase were upregulated upon the ClO 2 treatment and remained stable for a few days. ClO 2 treatment decreased hydrogen peroxide content and fruit senescence index, including browning and disease symptoms in pericarp during storage. It was concluded that the imbalance of redox status of ASA-GSH cascade involved senescence in ‘Daw’ longan, and ClO 2 could maintain the redox balance, leading to the alleviation and delay fruit senescence.